2018
DOI: 10.1007/s10151-018-1771-8
|View full text |Cite
|
Sign up to set email alerts
|

Transanal total mesorectal excision for rectal cancer: evaluation of the learning curve

Abstract: The learning curve of TaTME affected major (surgical) postoperative complications for the first 40 patients. A two-team approach decreased operative time and conversion rate. When implementing this new technique, a thorough teaching and supervisory program is recommended to shorten the learning curve and improve the clinical outcomes of the first patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 25 publications
2
144
5
1
Order By: Relevance
“…The extent of dissection in each approach usually differs from case to case, however, rectal transection and dissection of the extra-peritoneal part of the rectum is performed transanally. There are several potential benefits of the two-team approach over the one-team approach, including assistance with exposure of the operative field and/or enhanced comprehension of the surgical anatomy 7) . However, the two-team approach requires extra human and device resources that might not always be available with the exception of in specialized centers.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…The extent of dissection in each approach usually differs from case to case, however, rectal transection and dissection of the extra-peritoneal part of the rectum is performed transanally. There are several potential benefits of the two-team approach over the one-team approach, including assistance with exposure of the operative field and/or enhanced comprehension of the surgical anatomy 7) . However, the two-team approach requires extra human and device resources that might not always be available with the exception of in specialized centers.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…Laparoscopic right hemicolectomy with extended D3 lymph node dissection offers a good long-term outcome for colon cancer treatment [3]. Several approaches have been used when performing a laparoscopic right hemicolectomy but most are generally comparable [4].…”
Section: Supporting Informationmentioning
confidence: 99%
“…Those specific complications and difficulties highlight the need for structured and accredited training program. Several authors have addressed the proper training pathway to the incorporation of TaTME into clinical practice [19][20][21][22][23][24][25] .…”
Section: Training Programmentioning
confidence: 99%
“…Koedam et al [26] evaluated the learning curve of TaTME in 138 patients with rectal cancer over a 60-month period. The authors reported improvement in postoperative outcomes after the first 40 patients, showing a decrease in major postoperative complications from 47.5% to 17.5% and leakage rate from 27.5% to 5%.…”
Section: Training Programmentioning
confidence: 99%